Iron Deprivation Modulates the Exoproteome in Paracoccidioides brasiliensis - Souza, Aparecido Ferreira de; Pigosso, Laurine Lacerda; Silva, Lana O’Hara Souza; Galo, Italo Dany Cavalcante; Paccez, Juliano Domiraci; e Silva, Kleber Santiago Freitas; de Oliveira, Milton Adriano Pelli; Pereira, Maristela; Soares, Célia Maria de Almeida (Frontiers in Cellular and Infection Microbiology, 2022)
Fungi of the Paracoccidioides genus are the etiological agents of the systemic mycosis paracoccidioidomycosis and, when in the host, they find a challenging environment that is scarce in nutrients and micronutrients, such as Fe, which is indispensable for the survival of the pathogen. Previous studies have shown that fungi of this genus, in response to Fe deprivation, are able to synthesize and capture siderophores (Fe3+ chelators), use Fe-containing host proteins as a source of the metal, and use a non-canonical reductive pathway for Fe3+ assimilation. Despite all these findings, there are still gaps that need to be filled in the pathogen response to metal deprivation. To contribute to the knowledge related to this subject, we obtained the exoproteome of Paracoccidioides brasiliensis (Pb18) undergoing Fe deprivation and by nanoUPLC-MSE. One hundred and forty-one proteins were identified and out of these, 64 proteins were predicted to be secreted. We also identified the regulation of several virulence factors. Among the results, we highlight Cyb5 as a secreted molecule of Paracoccidioides in the exoproteome obtained during Fe deprivation. Cyb5 is described as necessary for the Fe deprivation response of Saccharomyces cerevisiae and Aspergillus fumigatus. Experimental data and molecular modeling indicated that Cyb5 can bind to Fe ions in vitro, suggesting that it can be relevant in the arsenal of molecules related to iron homeostasis in P. brasiliensis.